Comparison of a mathematical model to predict 10-km performance from the Conconi test and ventilatory threshold measurements - Petit, M. A.; Nelson, C. M.; Rhodes, E. C. (Canadian Journal of Applied Physiology, 1997)
The purpose of this study was to validate a mathematical model (MM) that evaluates the Conconi test and predicts 10-km race time. In addition, the relationship between ventilatory threshold (Tvent) determined from a laboratory test and heart rate deflection (HRd) from the Conconi test were examined. Seventeen trained runners performed the Conconi test, and performance times were predicted using a MM based on a logistics function. A correlational analysis indicated a highly significant relationship (r = .98, p < .01) between MM predicted time and actual time. Significant relationships were found between velocity at Tvent and HRd (r = .95, p < .01), and predicted times from each method (r = .96, p < .01). Heart rates from Tvent and HRd were also related (r = .79, p < .01). These results suggest that a MM of the Conconi test is a valid method of predicting 10-km performance and is closely related to traditional laboratory measures.